Evaluation of nutrient management for better growth, yield and economics of fenugreek - Suneetha, M Anitha, D V Swami, B P Kumar, D R S (Journal of Spices and Aromatic Crops, 2016)
A field experiment was conducted to study the effect of nutrient management combinations in fenugreek (Trigonella foenum-graecum). Growth as well as seed and straw yields of fenugreek were significantly influenced by different treatments. Application of recommended dose through inorganic form (50%) + neem cake @ 638 kg ha-1 + Rhizobium melilotii + phosphate solubilising bacteria (PSB) recorded the highest plant height of 34.98 cm, leaves of 82.35 and branches of 5.5 at the final harvest stage. This treatment also recorded significantly highest straw yields. The maximum seed yield, net returns and benefit cost ratio were obtained in the combination of 50% recommended dose of fertilizer (RDF) + poultry manure (PM) @1000 kg ha-1 + Rhizobium melilotii + phosphate solubilising bacteria (PSB).